PRAKTIK MANAJEMEN LABA : PERAN GOOD CORPORATE GOVERNANCE DAN FINANCIAL DISTRESS (STUDI PADA PERUSAHAAN PROPERTY DAN REAL ESTATE) - Siti Rohmah; Evllyshin Pakadang; Agus Riyanto; Pantas P Pardede; Nadiya Yunan; Nur Patul Auliah (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2025)
The purpose of this study was to determine the influence, both partially and simultaneously, between the independent board of commissioners, managerial ownership, audit committee and financial distress on earnings management in property and real estate companies listed on the IDX for the 2021-2023 period. The research method used in this study is to use the inferential method to analyze the relationship between variables with hypothesis testing. The data source in this study is in the form of secondary data obtained through the company's financial reports. The data analysis technique used is multiple linear regression. The results of this study indicate that the independent board of commissioners, managerial ownership, audit committee and financial distress partially affect earnings management, and simultaneously Good Corporate Governance consisting of an independent board of commissioners, managerial ownership, audit committee and financial distress has an effect on earnings management